Toward a Typology of the Client: A Latent Class Analysis Approach to the Consumption of Sex Work in the United States - Wakefield, Chris (The Journal of sex research, 2025)
Previous research on male clients of sex workers has emphasized the diversity of purchasing behaviors; however, we know little about how to organize or categorize this diversity quantitatively. I employed latent class analysis with survey data from cisgender male clients of primarily cisgender female sex workers in the United States to organize client consumption patterns by the type of venue used to contact sex workers and the frequency of using each venue. I found that patterns of consumption emerged around the frequency and context in which sex work is negotiated, generating six distinct patterns of buying: generalists, internet-only buyers, brothel-only buyers, experimenters, routinized buyers, and opportunists. I used multinomial logistic regression to identify relationships between latent class membership, known covariates, and self-reported motivations for purchase. Classes had small but significant demographic differences around age, income, marital status, arrest history, and international sex work engagement. Motivational differences were observed across classes, including the importance of emotional connection, practicing sexual skills, and relaxation. Implications for future research are discussed.